Male Genital Schistosomiasis Along the Shoreline of Lake Malawi: Baseline Prevalence and Associated Knowledge, Attitudes and Practices Among Local Fishermen in Mangochi District, Malawi - Sekeleghe A. Kayuni; Sekeleghe A. Kayuni; Sekeleghe A. Kayuni; Mohammad H. Alharbi; Peter Makaula; Fanuel Lampiao; Lazarus Juziwelo; E. James LaCourse; J. Russell Stothard (Frontiers Media S.A., 2021)
Male genital schistosomiasis (MGS) is an often-overlooked chronic consequence of urogenital schistosomiasis (UGS) associated with Schistosoma haematobium eggs and associated pathologies in the genital system of afflicted men. Despite the first formal description of MGS in 1911 by Madden, its epidemiology, diagnostic testing and case management of today are not well-described. However, since several interactions between MGS and the Human Immunodeficiency Virus (HIV) are known, there is renewed public health interest in MGS across sub-Saharan Africa (SSA). To shed new light upon MGS in Malawi, a longitudinal cohort study was set up among fishermen along the southern shoreline of Lake Malawi in Mangochi District, Malawi, to document its prevalence and assess mens' knowledge, attitudes and practices (KAP). After providing informed written consent, fishermen (n = 376) aged 18+ years (median age: 30 years, range: 18-70 years) were recruited and submitted urine and semen for point-of-care (POC) field and laboratory diagnostic parasitological tests. Individual questionnaires were administered to assess their KAP, with praziquantel (PZQ) treatment provided to all participants. Baseline prevalence of MGS (S. haematobium eggs in semen) was 10.4% (n = 114, median: 5.0 eggs per ml, range: 0.1-30.0) while for UGS (S. haematobium eggs in urine) was 17.1% (n = 210, median: 2.3 eggs per 10 ml, range: 0.1-186.0) and 3.8% were positive by POC circulating cathodic antigen (POC-CCA), indicative of a Schistosoma mansoni infection. Just under 10% of participants reported having experienced symptoms associated with MGS, namely genital or coital pain, or haemospermia. A total of 61.7% reported previous difficulties in accessing PZQ therapy, with 34.8% having received PZQ therapy before. There was a significant correlation between MGS infection and the frequency of fishing in a week (rho = −0.25, n = 100, p = 0.01). In conclusion, MGS is prevalent among local fishermen yet knowledge of the disease is poor. We therefore call for improved availability and accessibility to MGS diagnostics, PZQ treatment within ongoing control interventions. This will improve the lives and reproductive health of men, their partners and communities in this shoreline environment of Lake Malawi.